Turbot (Scophthalmus maximus) vs. VHSV (Viral Hemorrhagic Septicemia Virus): A Review - Pereiro, Patricia; Figueras, Antonio; Novoa, Beatriz (Frontiers in Physiology, 2016)
Turbot (S. maximus) is a very valuable fish species both in Europe and China. The culture of this flatfish is well stablished but several bacteria, viruses and parasites can produce mortality or morbidity episodes in turbot farms. Viral Hemorrhagic Septicemia Virus (VHSV) is one of the most threatening pathogens affecting turbot, because neither vaccines nor treatments are commercially available. Although the mortality in the turbot farms is relatively low, when this virus is detected all the stock have to be destroyed. The main goals that need to be improved in order to reduce the incidence of this disease is to know what are the strategies or molecules the host use to fight the virus and, in consequence, try to potentiate this response using different ways. Certain molecules can be selected as potential antiviral treatments because of their high protective effect against VHSV. On the other hand, the use of resistance markers for selective breeding is one of the most attractive approaches. This review englobes all the investigation concerning the immune interaction between turbot and VHSV, which until the last years was very scarce, and the knowledge about VHSV-resistance markers in turbot. Nowadays, the availability of abundant transcriptomic information and the recent sequencing of the turbot genome open the door to a more exhaustive and profuse investigation in these areas.